MUSIQUE CENTRE-AFRICAINE—Extrait du Volume “Afrique Equatoriale Francaise” de L’Encyclopédie Coloniale et Meritime—by Herbert Pepper, 20pp. (International Library of African Music, 1958)
pages: 87-88
Keywords: African Music